The Guantánamo Detention Camp and International Humanitarian Law - Marsili, M. (Rivista di Studi Politici Internazionali, 2025)
Through the reconstruction of the policies of the U.S. Administrations that have followed one another over the years (2002-2024), this paper retraces two decades of gross human rights violations in the Guantánamo detention camp and aims to preserve the memory of one of the most shameful episodes in American history. The article is mainly based on the review of the legal provisions adopted by the U.S. government, as well as on U.S. court orders. Abducted, forcibly removed from their families, held incommunicado, tortured, the prisoners held in the facility remained for years awaiting trial or release. Some of them died during detention. Over two decades after 9/11, Guantánamo is still open, and a few dozen people are still detained there.